LA PERCEPTION DES DYSFONCTIONNEMENTS DU DÉVELOPPEMENT URBAIN VUE PAR LES HABITANTS DE BATNA (ALGÉRIE) - BENYAHIA LAMIA; DRIDI HADDA; NACEUR FARIDA (Revue Roumaine de Géographie)
Perception of dysfunctions in the urban development view of Batna inhabitants (Algeria). The study aims to describe how the people of Batna feel urban dysfunction. Inspired by the approach of Veolia Observatory on urban lifestyles, this study is based on a questionnaire conducted among 416 residents of the town. The results of this research have established a real diagnosis of the dysfunctions of the city as seen and experienced by people. This investigation, gathering evidence, documents and experiments, revealed different perceptions of interviewed citizens’ knowledge and socio-cultural and demographic aspects.